Analysis of Abnormal Uterine Bleeding in Endometrium of Perimenopausal Women: AnHistopathological Study - Agrawal, Madhuri; Singhal, Ramkumar (Asian Journal of Medical Research, 2019)
Background: Abnormal uterine bleeding is one of the most common health problem encountered by women of perimenpausal age group. Hence; the present study was undertaken for assessing abnormal uterine bleeding in endometrium of perimenopausal women. Subjects and Methods: A total of 72 subjects were enrolled. Subjects with menstrual cycles of 21 to 35 days were enrolled. Subjects with duration of flow of 2 to 6 days were excluded from the present study, as they were considered as normal. Complete demographic details of all the subjects were obtained. Collection of the specimen was done for histopathologic assessment. Results: Abnormal uterine bleeding was clinical diagnosis in 30 patients, while it was pathologic diagnosis on 21 patients. Fibroid formation was clinical diagnosis in 20 patients, whereas on histopathologic examination, fibroid formation was found to be present in 15 patients. Proliferative phase was found to be present in 41.6 percent of the patients. Secretory phase was found to be preset in 20.8 percent of the patients. Hyperplasia was found to be present in 26.4 percent of the patients. Conclusion: The most common cause of abnormal uterine bleeding in perimenopausal women are benign lesions of endometrium and myometrium.